The Right to Observe and the Right to Resplendence in the Islamic City Image - Bahman Adibzadeh (صفه)
Any citizen has rights, and the Islamic city citizen is no exception. The present paper is written as a prologue to ‘limbs’ rights’, which is part of the Islamic city citizen’s ‘natural rights’, with reference to Imam Sajad’s  (p.b.u.h) Rights Prescript. Due to the wide scope of ‘limbs’ rights’, the present paper focuses on ‘ ‘eye’s right’ as one of the limbs, to seek its practicability in the country’s architectural and urban systems.  The image of the Islamic city should not only be responsive to the right to see or observe, but also a ground for resplendence. The contribution of the city to the eye’s right is through urban image, and this image is in turn created through an orderly relation between ‘the right to resplendence’ and ‘the right to observe’. Islamic teachings on respecting the right to resplendence and observe are, therefore, the basis for mandates and rights regarding the image of the Islamic city in the present text.It should be mentioned that acquiring the right to resplendence and observe will not be possible without paying due attention to the right to full reclaim (‘estifa’, or taking maximal advantage of someone or something) and full enjoyment (‘tamatoe’, or taking maximal advantage of someone or something based on certain limits and conditions) (Katouzian 2002).How, where, and to what extent the right to resplendence and observe arises and manifests itself depends on its limits as defined based on the right to ‘estifa’ and ‘tamatoe’. Success in creating such urban rights will have positive effects not only on the city’s physicality, but also on its social, cultural … relations.